2019
DOI: 10.1186/s12915-019-0639-3
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral heterogeneity in quorum sensing can stabilize social cooperation in microbial populations

Abstract: BackgroundMicrobial communities are susceptible to the public goods dilemma, whereby individuals can gain an advantage within a group by utilizing, but not sharing the cost of producing, public goods. In bacteria, the development of quorum sensing (QS) can establish a cooperation system in a population by coordinating the production of costly and sharable extracellular products (public goods). Cooperators with intact QS system and robust ability in producing public goods are vulnerable to being undermined by Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 67 publications
4
25
0
Order By: Relevance
“…We predicted that defectors would be less likely to evolve and rise to detectable frequencies in WT populations due to our previous competition results, as well as other reported mechanisms of cheater control such policing and metabolic constraint [15,[60][61][62][63][64]. We found that this prediction was partially correct in the conditions tested.…”
Section: Discussionsupporting
confidence: 52%
“…We predicted that defectors would be less likely to evolve and rise to detectable frequencies in WT populations due to our previous competition results, as well as other reported mechanisms of cheater control such policing and metabolic constraint [15,[60][61][62][63][64]. We found that this prediction was partially correct in the conditions tested.…”
Section: Discussionsupporting
confidence: 52%
“…In addition to nutrients, bacteria can also produce extracellular products that benefit neighboring cells. Although an individual cell experiences an energetic cost in metabolism, the production is beneficial for the surrounding population (Zhao et al, 2019). The production of these products occurs when bacteria are in a dense biofilm community where many of the surrounding cells are related organisms.…”
Section: Public Goodsmentioning
confidence: 99%
“…WT PAO1 or lasR mutant strains were well-mixed with K. pneumoniae at different ratios (1:99, 1:1, and 99:1) in 1.0 ml of sterile saline solution. Subsequently, 5 μl of inocula were separately spotted on disposable sterile petri dishes containing 20 ml of LB agar medium or modified M9 agar medium supplemented with 0.5% (w/v) of skim milk powder (Zhao et al, 2019). The plates were sealed by sealing films and then statically cultured at 37°C for different time periods.…”
Section: Methodsmentioning
confidence: 99%